Publication trends in neuroimaging of minimally conscious states - Alex Garnett; Grace Lee; Judy Illes (PeerJ, 2013)
We used existing and customized bibliometric and scientometric methods to analyze publication trends in neuroimaging research of minimally conscious states and describe the domain in terms of its geographic, contributor, and content features. We considered publication rates for the years 2002–2011, author interconnections, the rate at which new authors are added, and the domains that inform the work of author contributors. We also provided a content analysis of clinical and ethical themes within the relevant literature. We found a 27% growth in the number of papers over the period of study, professional diversity among a wide range of peripheral author contributors but only few authors who dominate the field, and few new technical paradigms and clinical themes that would fundamentally expand the landscape. The results inform both the science of consciousness as well as parallel ethics and policy studies of the potential for translational challenges of neuroimaging in research and health care of people with disordered states of consciousness.